Social media and mental health of undergraduate medical students of Mysuru: cross sectional study - Chaitali; Gohri, Jay; Hegde, Saurish; K. S., Sahana; Doddaiah, Sunil Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: Social media is a form of electronic communication, through which people can share ideas and information. With the advent of internet and social networking sites, humans have become social more virtually than in person. This has led to people living more isolated lives affecting one’s health. Hence the objective is to assess the effects of social media on students and factors associated. Methods: It was a Cross sectional study among 367 undergraduates from a medical college in Mysuru, over a duration of 2 months. A self-administered questionnaire with socio- demographic variables and a standard GHQ-12 (general health questionnaire) was used for the scoring of their distress levels. Descriptive statistics were taken and Chi-square test was done for statistical significance. Results: Out of 367 students, the mean age of students were 21.5 years. The prevalence suggestive of distress was found to be 72.4% (265), and severe psychological distress was found to be 3.27%. Among usage of apps, people using 1 app had 48.5% distress, 2 apps had 75.6% distress, 3 apps had 63.3% distress and 4 apps 74.2% distress. There was no significant association between factors and severity of distress. Conclusions: From the above study, we have shown that social media with all its influence has a negative impact on the students’ behavior. With this the youth need to be educated on its use and its limitations counselled regarding its ill effects and necessary tolls for seeking help be made available at their disposal.